Pengaruh Motivasi, Disiplin Kerja, dan Etos Kerja terhadap Kinerja Guru MTs Raudhatul Mujawwidin Kabupaten Tebo - Ika Febrianti Muanas; Muhammad Anas Maarif (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study investigated the influence of motivation, work discipline, and work ethic on teacher performance at MTs Raudhatul Mujawwidin. A quantitative research design with a survey approach was employed. Data were collected through questionnaires distributed to 32 teachers and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the aid of SPSS software. The results showed that all research instruments met the validity and reliability requirements, indicating that they were appropriate for data collection. The multiple linear regression analysis generated the following regression equation: Y = 0.959 + 0.186X₁ + 0.510X₂ + 0.073X₃. The partial hypothesis testing revealed that motivation (X₁) did not significantly influence teacher performance (t = 0.929, p = 0.361 > 0.05). Likewise, work ethic (X₃) had no significant effect on teacher performance (t = 0.492, p = 0.627 > 0.05). In contrast, work discipline (X₂) had a positive and statistically significant effect on teacher performance (t = 2.954, p = 0.006 < 0.05), with a regression coefficient of 0.510, indicating that work discipline was the most dominant predictor of teacher performance. Furthermore, the simultaneous hypothesis test demonstrated that motivation, work discipline, and work ethic collectively had a significant effect on teacher performance (F = 7.040, p = 0.001 < 0.05). The coefficient of determination (R²) was 0.430, indicating that 43% of the variance in teacher performance could be explained by the three independent variables, whereas the remaining 57% was influenced by other factors not examined in this study, such as school facilities, leadership style, work environment, and educational policies.